Aronia melanocarpa Products and By-Products for Health and Nutrition: A Review - Tomislav Jurendić; Mario Ščetar (Antioxidants, 2021)
Due to factors such as cultivar, fertilization, maturation or climate conditions, as well as the date of their harvest, chokeberries (Aronia melanocarpa) differ in their content of minerals, vitamins, carbohydrates, amino acids, organic acids, fats, aroma compounds and especially polyphenols, substances exerting a beneficial impact on health. The total content of the most important ingredients, polyphenolic compounds, influence many proven chokeberry activities like antioxidative, anti-inflammatory, hypotensive, antiviral, anticancer, antiplatelet, antidiabetic and antiatherosclerotic, respectively. Polyphenolic compounds such as anthocyanins, flavonoids, procyanidins and phenolic acids in different rates and amounts are responsible for all mentioned activities. In the human body, they undergo different biotransformative processes strengthening their bioactivity inside and outside cells. The popularity of chokeberry has been significant lately because of its effects on human health and not just because of its nutritional value. The main interest in this review has been refocused on the chokeberry benefits to human health, nutritional contribution of its components, particularly polyphenolic compounds, and its physiological effects.